2021
DOI: 10.1093/ecco-jcc/jjab153
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab and Infliximab Impair SARS-CoV-2 Antibody Responses: Results from a Therapeutic Drug Monitoring Study in 11 422 Biologic-Treated Patients

Abstract: Background and aims Infliximab attenuates serological responses to SARS-CoV-2 infection. Whether this is a class effect, or if anti-TNF level influences serological responses, remains unknown. Methods Seroprevalence and the magnitude of SARS-CoV-2 nucleocapsid antibody responses were measured in surplus serum from 11422 (53.3% (6084) male; median age 36.8 years) patients with immune-mediated inflammatory diseases, stored at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 31 publications
6
35
0
Order By: Relevance
“…On one hand, this decision could be supported by evidence of a lower serological response to vaccines or natural infection, related to either IBD itself 15 or IBD therapies, namely anti‐TNF agents. 16 , 17 On the other hand, if priority access is granted to people at higher risk of adverse COVID‐19 outcomes, should this apply to some or all IBD patients? To answer this question, this observational study investigated risk factors for adverse COVID‐19 outcomes in a large, nation‐wide cohort of IBD patients, and used multivariable analyses to build indices to identify patients at the relatively highest risk.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, this decision could be supported by evidence of a lower serological response to vaccines or natural infection, related to either IBD itself 15 or IBD therapies, namely anti‐TNF agents. 16 , 17 On the other hand, if priority access is granted to people at higher risk of adverse COVID‐19 outcomes, should this apply to some or all IBD patients? To answer this question, this observational study investigated risk factors for adverse COVID‐19 outcomes in a large, nation‐wide cohort of IBD patients, and used multivariable analyses to build indices to identify patients at the relatively highest risk.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, little is known about the effectiveness, side-effects, and safety of SARS-CoV-2 vaccination in IBD patients, especially in the case of required immunosuppressive therapies. Recent studies revealed attenuated immune responses to SARS-CoV-2 infection in patients treated with immunomodulating therapies (e.g., anti-TNF agents), suggesting an attenuated immune response following vaccination [14].…”
Section: Introductionmentioning
confidence: 99%
“…Protective immunity and vaccination will be critical to ending the COVID-19 pandemic, and a global vaccination programme is underway. Some evidence suggests TNF inhibitors may impair immune responses to pneumococcal, influenza, and viral hepatitis vaccinations [ 97 ]; thus, it is important to understand their impact in the context of COVID-19. The UK-based CLARITY study has shown that infliximab attenuated the serological response after natural infection, finding an inverse relationship between infliximab trough levels and seroconversion [ 84 , 97 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
“…Some evidence suggests TNF inhibitors may impair immune responses to pneumococcal, influenza, and viral hepatitis vaccinations [ 97 ]; thus, it is important to understand their impact in the context of COVID-19. The UK-based CLARITY study has shown that infliximab attenuated the serological response after natural infection, finding an inverse relationship between infliximab trough levels and seroconversion [ 84 , 97 ]. Lower seroconversion rates in infliximab-treated patients were also noted after a single SARS-CoV-2 vaccine dose, which could increase the likelihood of recurrent SARS-CoV-2 infection in affected patients [ 97 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
See 1 more Smart Citation